Polarization or Upgrading? Evolution of Employment in Transitionary Russia - Vladimir Gimpelson; Rostislav Kapeliushnikov (Institute for the Study of Labor (IZA), 2014)
This paper discusses the structural change in the Russian employment and explores whether the evolution of employment over 2000-2012 followed the scenario of progressive upgrading in job quality or brought about the polarization of jobs in terms of their quality. Jobs are defined here as occupation-industry cells and their quality is measured through relative earnings and education levels. Using detailed micro-data from a few complementary large scale surveys, we rank all jobs according to the earnings and educational criteria and divide these distributions into 5 quintiles. At the next stage, we explore dynamic changes in job quality and socio-demographic characteristics of workers in different quintiles. The paper rejects the polarization scenario and confirms the upgrading hypothesis.
Keywords: J31; J62; 330; job polarization; job upgrading; job quality; employment restructuring; Russia